Comparative wear study of plasma sprayed TiO2 and Al2O3–TiO2 on mild steels. (January 2016) - Ghazali, M.J.; Forghani, S.M.; Hassanuddin, N.; Muchtar, A.; Daud, A.R.
Abstract: With good combination of hardness, ductility, and wear resistance, TiO2 coatings are one of the most potential hard ceramic coatings. TiO2 in an Al2 O3 coating had increases the wear resistance which has contributed to an increase in the fracture toughness and decrease in the coefficient of friction. The specific wear rates of pure TiO2 coatings are found to be ranging from 1.62×10 −5 –4.19×10 −5  cm 3 /N m whereas the Al2 O3 /TiO2 coatings are in the range of 2.0×10 −3  cm 3 /N m to 28.0×10 −3  cm 3 /N m. This concludes that the TiO2 coatings are most preferable in improving wear resistance. Highlights: Unique feature like the bi-modal structures were spotted on both ceramic coating deposition. Bi-modal structure is important in determining microhardness and wear resistance. Combination of semi and complete melted regions improves fracture toughness In short, the TiO2 coatings are considered as one of the most potential hard ceramic coatings.